2023
DOI: 10.3847/1538-3881/acdd56
|View full text |Cite
|
Sign up to set email alerts
|

Inner Planetary System Gap Complexity is a Predictor of Outer Giant Planets

Abstract: The connection between inner small planets and outer giant planets is crucial to our understanding of planet formation across a wide range of orbital separations. While Kepler provided a plethora of compact multiplanet systems at short separations (≲1 au), relatively little is known about the occurrence of giant companions at larger separations and how they impact the architectures of the inner systems. Here, we use the catalog of systems from the Kepler Giant Planet Search to study how the architectures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The current planet sample remains too small to fully establish the correlation between inner small planets and outer giant planets and explore its dependence on properties of the host stars and the planetary systems (see some early attempts by Zhu 2019 andWeiss 2023), making it difficult to test predictions of formation models (e.g., Schlecker et al 2021;Best et al 2024;Bitsch & Izidoro 2023). The ongoing RV follow-up observations of transiting systems (e.g., Bonomo et al 2023;Van Zandt et al 2023;Weiss et al 2024) and upcoming Gaia astrometric detections (e.g., Perryman et al 2014;Espinoza-Retamal et al 2023) aided by careful statistical analysis will be helpful in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The current planet sample remains too small to fully establish the correlation between inner small planets and outer giant planets and explore its dependence on properties of the host stars and the planetary systems (see some early attempts by Zhu 2019 andWeiss 2023), making it difficult to test predictions of formation models (e.g., Schlecker et al 2021;Best et al 2024;Bitsch & Izidoro 2023). The ongoing RV follow-up observations of transiting systems (e.g., Bonomo et al 2023;Van Zandt et al 2023;Weiss et al 2024) and upcoming Gaia astrometric detections (e.g., Perryman et al 2014;Espinoza-Retamal et al 2023) aided by careful statistical analysis will be helpful in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Chance et al (2022) found a larger rate of giant impacts for single-transiting systems, which could produce an offset in the radius between single-and multiple-transiting systems. He & Weiss (2023) quantified an impact upon inner system architecture from the presence of an outer giant planet; potentially the presence of an outer companion could also change planet size as well as planetary spacing. Singletransiting systems may have an unknown outside companion in their system that constrains the growth of the inner transiting planet.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the paradigms thus discussed present comparatively quiescent and lowerentropy dynamical pathways for the assembly of volatile-rich worlds compared to their rocky counterparts, thereby collectively arguing for a greater uniformity in planetary spacing for the former in direct opposition to the trends presented in this work. It has been recently demonstrated that the presence of giant planetary companions can disrupt the spacing uniformity of the inner system (He & Weiss 2023) though such a starkly preferential occurrence of these companions for volatile-rich systems cannot be accurately constrained with regard to our primary samples. As such, it remains to be determined if further analytical frameworks or simulations may successfully recover this surprising dichotomy in spacing uniformity.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%